Role of sympathetic nerve activity in the process of fainting - Iwase, Satoshi; Nishimura, Naoki; Mano, Tadaaki (Frontiers in Physiology, 2014)
Syncope is defined as a transient loss of consciousness and postural tone, characterized by rapid onset, short duration, and spontaneous recovery, and the process of syncope progression will be described with two types of sympathetic change. Simultaneous recordings of microneurographically recorded MSNA and continuous and noninvasive blood pressure measurement have disclose what is going on in the course of progression of the syncope. Vasovagal or neurally mediated syncope, three stages are identified in the course of syncope onset, oscillation, imbalance, and catastrophe phases. The vasovagal syncope is characterized by the sympathoexcitation, followed by vagal overcome via the Bezold-Jarisch reflex. Orthostatic syncope is caused by the response failure or lack of sympathetic nerve activity toward the orthostatic challenge followed by the fluid shift, and subsequent cerebral low perfusion. Four causes are considered for the compensatory failure, which triggers the orthostatic syncope; hypovolemia, increased pooling in the lower body, failure to activate the sympathetic activity, and failure of vasoconstriction against sympathetic vasoconstrictive stimulation. Many pathophysiological conditions were described in the viewpoint of 1) exaggerated sympathoexcitation and 2) failure to activate the sympathetic nerve. We conclude that the sympathetic nervous system can control the cardiovascular function, and its failure resulted syncope, however, responses of the system by microneurographically recorded MSNA would determine the pathophysiology of the onset and progression of syncope, explaining the treatment effect that could be achieved by the analysis of this mechanism.